THE IMPACT OF TECHNOLOGY AND MODERN LIFE ON 20TH- CENTURY LITERATURE - Eldorbek Erkin og’li Khamitov; Nurymbetova Zumrad Ruslanovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This research explores how technological progress and the fast-paced lifestyle of the modern era shaped the evolution of literature in the 20th century. As innovations in science, industry, communication, and media transformed human existence, authors reacted by reshaping traditional literary forms and themes. The study discusses how advancements such as mechanization, urban expansion, global communication systems, and the beginnings of digital technology influenced new ways of depicting time, space, identity, and human consciousness in literary works. It also examines how writers adopted unconventional narrative structures, including fragmented storytelling, psychological interiority, experimental techniques, and dystopian imagery, to capture the complexity of an increasingly modernized society. The analysis focuses on major literary figures who addressed issues of isolation, the weakening of individual identity, the accelerated rhythm of life, and the conflict between technological growth and human values. Ultimately, the research argues that 20th-century literature served both as an artistic reaction to technological change and as a medium for critically interpreting the dramatic shifts of the modern world.